Region Effective Production Assets and Their Assessment By The Production Function Method - Gorbunov, Vladimir Konstantinovich; Krylov, Vladimir Pavlovich (Economy of Regions, 2015)
Effective production assets of region or country are the assets that really commit in production development. According to the neoclassical rationality principle of economic agents, the effective assets have to be considered in the production functions representing the mathematical models of large production facilities (production associations, sectors, economies of regions and countries). Existence of adequate production function allows making the deep economic analysis of facility and solving planning and forecasting problems. However, the researchers have only information on the balance funds, which are often poorly reflecting the real state of economy. The indistinct effective fund concept can be formalized and assessed quantitatively within the method of the production functions (PF) on the basis of V. K. Gorbunov and A. G. Lvov’s model (2012) of the standard macroeconomic PF development, one of which factors - the capital according to the statistical information on production investments. Effective funds are estimated together with the PF parameters and the main indicators of fund dynamics: amortization and initial value. In the article, the coefficient of marketability on investment, which is a share of real use of the allocated production investments, is additionally introduced into the dynamic equation. The comprehensive assessment results of the PF parameters and effective funds for economies of the Volga and Ural Federal Districts with use of several classes of two-factorial PF are given. As the second factor, the work and energy consumption are alternatively considered. As the result of development of region PF, the macroeconomic indicators: average and marginal returns of factors, factorial elasticity, marginal rate of factor substitution, elasticity of substitution, are calculated. It increases the quality of the quantitative analysis of regional economies and objectivity of their comparison.